Radiobasilic transposition arteriovenous fistula (RBTAVF): an effective but less frequently used haemodialysis vascular access- A Case Report - Riaz, Tahira; Zia Ur Rehman; Saood Ahmed Riaz (Journal of the Pakistan Medical Association, 2022)
Radiobasilic transposition arteriovenous fistula (RBTAVF) is often ignored as an option for haemodialysis access. We present the case of a 57-year-old male patient who presented at the AKUH vascular clinic, Karachi, for the creation of long-term haemodialysis vascular access. He had small-sized forearm cephalic vein (1.5 mm), but reasonable sized basilic vein. He underwent successful RBTAVF. Most of the guidelines recommend brachiocephalic fistula (BCF) as the second choice following radiocephalic AVF. This case recommends the inclusion of RBAVF as the second choice for vascular access in international guidelines, in addition to BCF and BBF. Keywords: Chronic kidney disease, Fistula, Haemodialysis access.